Development and Psychometric Evaluation of an Instrument Assessing Barriers to Growth Hormone Treatment (BAR-GHT) - de Zwaan, Martina; Fischer-Jacobs, Josefine; Wabitsch, Martin; Reinehr, Thomas; Meckes-Ferber, Stefanie; Crosby, Ross D. (Frontiers in Endocrinology, 2020)
Purpose: This paper presents development and validation of a new patient reported outcome measure (PRO), the Barriers to Growth Hormone Therapy (BAR-GHT) in a patient (children/adolescent) and a parent version. The BAR-GHT was developed to measure problems and potential barriers to GHT. Methods: The development and validation of the BAR-GHT was conducted according to the Food and Drug Administration (FDA) Guidance on the development of PROs. Concept elicitation included a literature review and open-ended interviews with young patients, parents, and clinical experts. Qualitative data were analyzed based on grounded theory principles and draft items were rated in terms of their importance and clarity. The instruments underwent psychometric validation in a German clinic-based patient population of children and adolescents who inject themselves and in a parent sample who inject their child. The statistical analysis plan included exploratory factor analysis, reliability, and validity. Results: 29 patients, 22 parents, and 4 clinical experts participated in the concept elicitation, 156 children and adolescents age 8 to 18 years and 146 parents completed the validation study. Exploratory factor analysis resulted in six domains: Fear, Public Embarrassment, Annoyance, Daily Routine, Supplies, and Travel. Internal consistencies and test-retest reliabilities of the total score of both the patient version and the parent version were > 0.8. Convergent and discriminant validity was demonstrated. Conclusions: The final 19-item BAR-GHT for patients aged 8-18 years and the 16-item version for parents can be considered reliable and valid PROs of barriers to GHT.